The DNA Sequence Encoding Actin (ACT1) of Pandan (Benstonea sp.) - Roslim, Dewi Indriyani; Herman, Herman (Journal of Tropical Life Science, 2019)
One of housekeeping genes is actin gene. This gene is frequently used in gene expression studies as an internal control. The DNA sequence encoding actin from Pandan (Benstonea sp.) clone Riau has not been reported, therefore, this study investigated the DNA sequence encoding actin isolated from Benstonea sp. clone Riau. Total DNA isolation was performed in fresh leaves, total RNA isolation from stem, total cDNA synthesis, polymerase chain reaction using degenerate actin primer, electrophoresis, cloning, transformation, blue white colony selection, colony PCR, sequencing, data analysis using BioEdit and MEGA6 softwares and BLASTn program. The partial DNA sequence encoding actin from Benstonea sp. clone Riau obtained was 1,403 bp. The sequence was grouped as part of actin1 (ACT1) and it was consisted of two exons and one intron. The predicted coding and peptide sequences were 616 bp and 205 amino acids, respectively.Â The predicted coding sequence had 90% similarity to some ACT1 mRNA from some plants species but none of which belongs to Benstonea genus or Pandanaceae family. The deduced peptide sequence had similarity to some ACT1 peptide from some plant species of up to 99% and also none of them belongs to Benstonea genus or Pandanaceae family. Thus, the partial ACT1 gene obtained in this study was the first sequence reported from Benstonea genus. Furthermore, this sequence can be used as a reference to isolate actin genes from other species within Benstonea genus for gene expression analysis purposes.